Evaluation of ctxA gene expression of Vibrio cholerae strain 569B in the production of cholera vaccine - Vorobyova, Svetlana A.; Gaeva, Anna V.; Durakova, Oksana Sergeevna; Kritsky, Andrey A.; Gromova, Olga V.; Volokh, Oksana Alexandrovna (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология, 2022)
Cultivation of production strains of Vibrio cholerae is one of the most important stages in the production of cholera bivalent chemical vaccines. In the production of immunobiological preparations, it is necessary to use producer strains with stable properties that persist in a number of generations. The aim of this study was to evaluate the expression of the ctxA gene using molecular genetic methods of the V. cholerae 569B producing strain. By PCR with electrophoretic accounting of the results, the presence of this strain of the ctxA gene in the chromosome was established. The expression of this gene in all hourly samples of culture fluid was recorded by the method of PCR with reverse transcription, taking into account the results in real time and digital drip PCR. Immunochemical methods confirmed the presence of cholera toxin in the samples, with a maximum mark at the ninth hour, which corresponded to the maximum indicators of the “concentration of microbial cells”. Thus, molecular genetic methods have shown the stability of the production strain V. cholerae 569B in samples of 4 independent cultivations.